Mandibulotomy: an analysis of its morbidities - Nabil, Syed; Nazimi, Abdul Jabar; Nordin, R.; Hariri, Firdaus; Mohamad Yunus, M.R.; Zulkiflee, Abu Bakar (Elsevier, 2018)
The mandibulotomy is a procedure that was developed to improve access in tumour resection. This study aimed to investigate the complications associated with mandibulotomy and analyze factors that could affect the risks of developing these complications. The hospital records of all patients who underwent a mandibulotomy as part of their tumour ablative surgery at two major centres in Malaysia were reviewed retrospectively. Demographic, clinical, and complications data were recorded and analyzed. Early postoperative complications occurred in 46.5% of the patients and post-radiation therapy complications in 16.1%. Wound dehiscence (27.9%) and inferior alveolar nerve injury (25.6%) were the common early postoperative complications. Dental injuries (9.7%) and plate exposure/infection (9.7%) were the common post-radiation therapy complications. Furthermore, inferior alveolar nerve injury and early abscess formation were significantly associated with the site of the mandibulotomy. The T-stage of a tumour but not the site of mandibulotomy was significantly associated with tumour margin clearance. Mandibulotomy does pose an added risk of complications for a patient undergoing tumour surgery. The benefits of mandibulotomy in terms of gaining margin clearance could not be proven in this study. The site of mandibulotomy appears to increase the risk of developing an inferior alveolar nerve injury.